Electrohydraulic effect as an example of electrophysical technologies application in the oil industry. (November 2019) - Drozdov, A N; Narozhnyy, I M; Pak, D X; Ludupov, V B; Zemlianskii, G S
Abstract: This work was devoted to studies of electrohydraulic effect applicability in the oil industry. The major aim was to determine if the effect would be really useful in cleaning field pipelines from different precipitations such as calcium and barium sulphates, calcium and magnesium carbonates, sodium chloride salts and also tar and paraffin. In addition to it, another fields of possible applicability of the electrohydraulic effect were supposed to be find. Realisation of purposes put was achieved though reconstituting Lev Yutkin's layout for electrohydraulic impact and conducting several special experiments. Their thoughtful description with necessary accompanying illustrations can be find at the pages of this article. Results of experiments carried out, have proved the electrohydraulic impact effectiveness as a mean for cleaning pipes. Moreover, some results gave a reason to think that the effect worth applying to for increasing of the wellbore zone permeability as well as for extracting of solid minerals.